Pembinaan Karakter Unggul: Pengembangan Instrumen Inovatif Bernalar Kritis dan Karakter Mandiri dalam Ranah Topik Peredaran Darah Manusia - Esty Setyo Utaminingsih; Ellianawati; Muhammad Habib Ramadhani; Maria Ayu Puspita; Sri Sumartiningsih; Muhamad Subhi Apriantoro; Aldi Ihsandi (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to develop a critical reasoning and independent character instrument on the topic of human blood circulation. The method used was research and development (R&D) with a 4D model (Define, Design, Develop, and Disseminate). The results showed that the validity value of the content of critical reasoning instruments obtained a final value of 0.97, while independent instruments obtained a value of 1, which was perfect. Judging from empirical validity, vital and independent reasoning instruments were declared valid because they had a value above 0.355 from 31 students tested. Critical and independent reasoning instruments were declared reliable. The Alpha Cronbach value >0.70 had good distinguishing power because the value of the Corrected Item-Total Correlation did not exceed the Alpha Cronbach value. Developing assessment instruments for a critical and independent character in human blood circulation for fifth-grade elementary students was successful, demonstrating high validity and reliability, and held the significant potential to enhance science education through technology integration.